Capabilities and Challenges of Mobile Computing in Construction Industry - Kong, Sio Kah; Leong, Leonard, Jun Jie (INTI International University, 2022)
Mobile computing can be defined as a new term of technology, devices, and services that allow transmission of data, voice, and video in wireless systems. Although mobile computing has many advantages in the construction industry, but some of the users do not exactly know what is the true function of mobile computing that can apply to the construction industry. Consequently, the users only use their mobile computing to perform easy tasks in the construction so the application of mobile computing in the construction industry is low. Problems such as slow progress of site management, difficulty in accessing data and information, human error are due to the low or non application of mobile computing. The aim of this study is to evaluate the capabilities and challenges of mobile computing in construction industry in order to provide convenience and efficiency to the user in the construction industry. In the collection of primary data, a survey questionnaire is sent to the target respondents in the states of Kuala Lumpur and Selangor. The collected data are presented in Relative Importance Index (RII) and one sample t-test. The result shows that better project management is the most significant capability of mobile computing in construction industry, while cost of technologies and software is the most serious challenge in applying mobile computing in construction industry.